PENGEMBANGAN PEMERTAHANAN BAHASA JAWA MELALUI BUDAYA LOKAL GUYUB TUTUR DALAM KAJIAN ANTROPOLINGUISTIK - Akhmad T Tabrani; Luluk Sri A Prasetyoningssih (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to yield a product for the Javanese language maintenance through local culture in speech community in an anthropolinguistic study. This research anddevelopment study used the Recursive, Reflective, Design, and Development (R2D2)design. The development procedure consisted of four steps, i.e. designing a prototype,testing the prototype (through expert judgment and field testing), revising the prototype,and in a large scale producing a DVD of the Javanese language maintenance throughlocal culture in speech community. The data were analyzed by means of expert judgmentand field testing using the mean score analysis technique. The research and developmentproduct is a DVD of the Javanese language maintenance through local culture in speechcommunitysatisfying the acceptability requirement. The product becomes an officialdocument for the local government and related parties as a reference for the Javaneselanguage maintenance. The Java language as part of local culture is a cultural heritagethat must be preserved. To preserve local culture, cultural maintenance against externalinfluences is necessary by completely, authentically, and officially documenting it. Keywords: Javanese language maintenance, local culture, speech community, anthropolinguistics